DAMPAK FINTECH TERHADAP PERUBAHAN PERILAKU KONSUMEN DALAM AKSES LAYANAN KEUANGAN DIGITAL - Reo Zaputra (WORLDVIEW ( Development economic and sharia studies journal ), 2025)
The development of information technology has brought significant changes across various sectors of life, including the financial sector. Financial technology (fintech) has emerged as an innovation capable of disrupting traditional financial systems and offering fast, efficient, and easily accessible solutions for the public. This study aims to analyze the impact of fintech on changes in consumer behavior in accessing digital financial services. Using a descriptive qualitative approach and a literature review from various sources, the study shows that fintech has transformed consumer behavior from relying on conventional financial services to embracing digital ones. The positive impacts include increased financial inclusion, time efficiency, and ease of access. However, there are also negative effects, such as rising consumerism, dependence on technology, and low financial literacy among the public. Therefore, proper education and regulation efforts are needed so that the development of fintech can be utilized optimally and sustainably.